Investment, Islamic bank and financial design from Malaysian listed firms / Masturah Ma'in and Nor Shahrina Mohd Rafien - Ma'in, Masturah; Mohd Rafien, Nor Shahrina (Research Management Institute (RMI), 2013)
This paper examines the link between financial design and Islamic bank variables on firm investment. It is aimed to support additional empirical evidence based on previous studies. The firm-level data for Malaysian Shariah listed firms between 2000 and 2010 are used. This paper also utilizes the same estimation method i.e. generalised method of moments for dynamic panel data, as proposed by Arellano and Bover (1995). The findings show that: first, the investment of Shariah listed firms are positively related to the development of the banking system and the capital market. Second, the cash flow shows a negative impact on investment of firms. Third, the debt asset ratio has a negative impact on firm investment. Fourth, BaP Bithaman Ajil and Ijarah financing show a negative effect on investment of firm. Fifth, the zakah variable shows a mixed result on firm investment.